A rare case of isoniazid induced sideroblastic anemia - Hari, Arjun B.; Chawla, Kunal; Dessai, Rishikesh; Gulati, Shipra (International Journal of Research in Medical Sciences, 2023)
Sideroblastic anemia is a rare cause of anemia. Most of it accounts for the genetic cause, while drug induced is still uncommon. Our patient, a 20 year old female, is a known case of right frontal tuberculoma on ATT presented with complaints of generalized weakness and loss of appetite. On evaluation, she was found to have severe anemia and bone marrow studies confirmed it to be sideroblastic anemia. On revisiting the history, it was noted that she was not taking pyridoxine supplements as advised along with antitubercular drugs. Our patient is one among the few documented cases of Isoniazid induced sideroblastic anemia.This case needs attention because it is a preventable cause of anemia and the clinicians need to be aware about the compliance of the patient with the supplementary drugs.